A Concentrations Of pH, Chromium, and MPN Coliform Parameters in Alkaline Water - Fitri Rokhmalia; Pratiwi Hermiyanti (International Journal of Advanced Health Science and Technology, 2022)
Humans need water for life and up to 70% of the human adult body is water. Consuming enough mineral water for the body can help the digestive process, regulate metabolism, regulate food substances in the body, and regulate body balance. The aim of the study was to analyze the levels of biological and chemical parameters in alkaline water with various trademarks in Surabaya with the code 1, 2, 3, 4. This was an experimental study with the posttest only control group design. Research data were analyzed using one-way ANOVA to assess levels of biological (MPN Coliform) and chemical (total chromium) parameters in alkaline water (1, 2, 3, 4). The E. Coli parameter in 4 brands of alkaline water (1, 2, 3 and 4) met the requirements according to the standard, namely 0 colonies/100 ml. Chemical parameters such as total chromium met the standard with ±0.001-0.01 mg/l. In accordance with the results of the analysis, the process of making and producing alkaline water from various brands under study on the market were in accordance with Good Food Production Methods (GFPM), thus MPN Coliform contents were found. Recommendations for researchers are to conduct further research with different alkaline water trademarks and in other cities with a wider scope. For the public, people are urged to be more selective and smarter in choosing alkaline water so as to gain benefits in line with the purchasing power of middle and lower economic class.